ANALYSIS OF STUDENTS' LEARNING DIFFICULTIES IN MATHEMATICS SUBJECTS: A CASE STUDY IN HIGH SCHOOL STUDENTS - Gunawan, Gunawan; Musodiqoh, Ummu Atiyatul; Kusuma, Jaka Wijaya; Purwanto, Joko (Yayasan Education and Social Center, 2025)
This study analyses students' mathematics difficulties at SMA Negeri 1 Mesuji Raya, Lampung. This study uses a qualitative approach with a case study design involving 30 students. The collection was carried out through classroom observation and in-depth interviews. Data analysis includes data reduction, data presentation, and conclusions. The results show that learning mathematics is difficult due to internal and external factors. Internal factors include anxiety and student learning motivation. External influence factors include the quality of teaching methods and the support of the learning environment. The recommendations included teacher training and increased student support to address learning difficulties effectively. This study sheds a deeper understanding of the importance of holistic support in improving mathematics learning at the secondary level. The results of the study support efforts to improve the quality of education through a more structured and comprehensive strategy.